Satisfaction of user by facility provided at rest and service area in Kelantan / Mohamad Faiz Sa'ari and Norakmarwati Ishak - Sa'ari, Mohamad Faiz; Ishak, Norakmarwati (2020)
One of the important elements in a user's satisfaction level towards facilities provided is the user satisfaction of facilities. Rest area is a public facility, located next to a large thoroughfare such as a motorway, expressway, or highway, at which drivers and passengers can rest, eat, or refuel without exiting onto secondary roads. Other names include, motorway service area, travel plaza, rest stop, service area, rest and service area (RSA). Facilities at the rest and services area may include parks, like areas, fuel stations, public toilets, restaurants and other facilities. Along some highways and roads are services known as wayside parks, roadside parks, or picnic areas. Besides, user's satisfaction is defined as a measurement that determines how efficient users are with a facility provided, services and capabilities. User's satisfaction information, including surveys and ratings, can help a company determine how to best improve or change its products and services. Therefore, the aim of this research is to increase the satisfaction level of the users on facilities provided at the rest and service area in Kelantan. Specifically, there are three rest and service areas that were chosen to do the findings in Kelantan. The objectives of this research are to identify types of facility provided, to determine the level of user satisfaction on facilities and to suggest on the improvement of facilities provided at the rest and services area. An observation was conducted with the aid of a questionnaire which by using Google Forms and 97 questionnaires were distributed among the users of the rest and service area in Kelantan. As a whole, this research provides an understanding and importance of the facilities provided at the rest and service area as well as to increase the satisfaction level of the users on facilities provided at the rest and service area in Kelantan.